Cas9 Contributes to Group B Streptococcal Colonization and Disease - Spencer, Brady L.; Deng, Liwen; Patras, Kathryn A.; Burcham, Zachary M.; Sanches, Glenda F.; Nagao, Prescilla E.; Doran, Kelly S. (Frontiers in Microbiology, 2019)
Group B Streptococcus (GBS) is a major opportunistic pathogen in certain adult populations, including pregnant women, and remains a leading etiologic agent of newborn disease. During pregnancy, GBS asymptomatically colonizes the vaginal tract of 20-30% of healthy women, but can be transmitted to the neonate in utero or during birth resulting in neonatal pneumonia, sepsis, meningitis, and subsequently 10-15% mortality regardless of antibiotic treatment. While various GBS virulence factors have been implicated in vaginal colonization and invasive disease, the regulation of many of these factors remains unclear. Recently, CRISPR-associated protein-9 (Cas9), an endonuclease known for its role in CRISPR/Cas immunity, has also been observed to modulate virulence in a number of bacterial pathogens. However, the role of Cas9 in GBS colonization and disease pathogenesis has not been well-studied. We performed allelic replacement of cas9 in GBS human clinical isolates of the hypervirulent sequence-type 17 strain lineage to generate isogenic Δcas9 mutants. Compared to parental strains, Δcas9 mutants were attenuated in murine models of hematogenous meningitis and vaginal colonization and exhibited significantly decreased invasion of human brain endothelium and adherence to vaginal epithelium. To determine if Cas9 alters transcription in GBS, we performed RNA-Seq analysis and found that 353 genes (>17% of the GBS genome) were differentially expressed between the parental WT and Δcas9 mutant strain. Significantly dysregulated genes included those encoding predicted virulence factors, metabolic factors, two-component systems (TCS), and factors important for cell wall formation. These findings were confirmed by qRT-PCR and suggest that Cas9 may regulate a significant portion of the GBS genome. We studied one of the TCS regulators, CiaR, that was significantly downregulated in the Δcas9 mutant strain. RNA-Seq analysis of the WT and ΔciaR strains demonstrated that almost all CiaR-regulated genes were also significantly regulated by Cas9, suggesting that Cas9 may modulate GBS gene expression through other regulators. Further we show that CiaR contributes to GBS vaginal colonization and persistence. Altogether, these data highlight the potential complexity and importance of the non-canonical function of Cas9 in GBS colonization and disease.